2018
DOI: 10.1371/journal.pone.0197669
|View full text |Cite
|
Sign up to set email alerts
|

Widespread anatoxin-a detection in benthic cyanobacterial mats throughout a river network

Abstract: Benthic algae fuel summer food webs in many sunlit rivers, and are hotspots for primary and secondary production and biogeochemical cycling. Concerningly, riverine benthic algal assemblages can become dominated by toxic cyanobacteria, threatening water quality and public health. In the Eel River in Northern California, over a dozen dog deaths have been attributed to cyanotoxin poisonings since 2000. During the summers of 2013–2015, we documented spatial and temporal patterns of cyanotoxin concentrations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 66 publications
(90 reference statements)
10
74
3
Order By: Relevance
“…The concentrations of anatoxins, NOD-R and MCYs were consistent with data in previous studies from these sites [16, 28], with anatoxin concentrations five times greater than microcystin/nodularin concentrations. Solid-phase adsorption toxin tracking samplers (SPATTs) in the Eel River accumulated ATX and MCYs in 53% – 54% and 41% – 76% of samples for each toxin, respectively [16].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The concentrations of anatoxins, NOD-R and MCYs were consistent with data in previous studies from these sites [16, 28], with anatoxin concentrations five times greater than microcystin/nodularin concentrations. Solid-phase adsorption toxin tracking samplers (SPATTs) in the Eel River accumulated ATX and MCYs in 53% – 54% and 41% – 76% of samples for each toxin, respectively [16].…”
Section: Discussionsupporting
confidence: 90%
“…The concentrations of anatoxins, NOD-R and MCYs were consistent with data in previous studies from these sites [16, 28], with anatoxin concentrations five times greater than microcystin/nodularin concentrations. Solid-phase adsorption toxin tracking samplers (SPATTs) in the Eel River accumulated ATX and MCYs in 53% – 54% and 41% – 76% of samples for each toxin, respectively [16]. The site with the highest concentrations of both anatoxins and NOD-R was dominated by Anabaena , a finding that contrasts with that of Bouma-Gregson et al [16], who found no differences in ATX concentrations between Anabaena and Microcoleus dominated mats, although the authors only measured ATX, not dhATX so may have underestimated the total anatoxin concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Anatoxin-a and homoanatoxin-a are potent neurotoxins produced by some planktonic and benthic strains of the genera Anabaena, Oscillatoria, Aphanizomenon and Cylindrospermum (Bouma-Gerson et al, 2018). Indeed, numerous fatal intoxications of animals, by anatoxin-a and homoanatoxin-a, have been reported all over the world (Gugger et al, 2005; Puschner et al, 2010; Wood et al, 2007).…”
Section: Introductionmentioning
confidence: 99%